Effects of Bu Shen Hua Zhuo formula on the LPS/TLR4 pathway and gut microbiota in rats with letrozole-induced polycystic ovary syndrome - Wang, Yang; Xiao, Hui; Liu, Yanxia; Tong, Qing; Yu, Yanyan; Qi, Bing; Bu, Xiaoling; Pan, Tianyuan; Xing, Yu (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in gynecology. Traditional Chinese medicine (TCM) is widely used for the treatment of PCOS in China. The Bu Shen Hua Zhuo formula (BSHZF), a TCM decoction, has shown great therapeutic efficacy in clinical practice. However, the mechanism underlying BSHZF function in PCOS remains unclear. This study aimed to identify the potential mechanisms of action of BSHZF in the treatment of PCOS. PCOS-model rats treated with letrozole were administered different doses of BSHZF, metformin, and 1% carboxymethylcellulose. Serum sex hormone, fasting blood glucose, and fasting insulin levels were measured, and the morphology of the ovaries was observed in each group, including the normal group. The structure and abundance of the gut microbiota in rats were measured using 16S rRNA gene sequencing. Toll-like receptor 4 (TLR4) and phospho-NF-κB p65 levels in the ovarian tissue of the rats were detected using western blotting. Furthermore, levels of LPS and inflammatory cytokines TNF-α, IL-6, and IL-8 in the serum of rats were detected by ELISA. The results showed that BSHZF administration was associated with a decrease in body weight, fasting blood glucose, fasting insulin, and testosterone and changes in ovarian morphology in PCOS-model rats. Moreover, BSHZF was associated with an increase in the α-diversity of gut microbiota, decrease in the relative abundance of Firmicutes, and increase in Lactobacillus and short chain fatty acid-producing bacteria (Allobaculum, Bacteroides, Ruminococcaceae_UCG-014). Furthermore, BSHZF may promote carbohydrate and protein metabolism. In addition, BSHZF was associated with a decrease in the serum level of LPS and TLR4 expression, thereby inhibiting the activation of the NF-κB signaling-mediated inflammatory response in ovarian tissue. Therefore, the beneficial effects of BSHZF on PCOS pathogenesis are associated with its ability to normalize gut microbiota function and inhibit PCOS-related inflammation.